Leptomeningeal enhancement in magnetic resonance imaging predicts poor prognosis in lung adenocarcinoma patients with leptomeningeal metastasis. Issue 7 (3rd March 2022) - Gao, Xiaoxing; Pan, Ruili; Chen, Minjiang; Zhao, Jing; Zhong, Wei; Wang, Hanping; Si, Xiaoyan; Zhang, Xiaotong; Zhang, Li; Xu, Yan; Wang, Mengzhao
Abstract: Background: To investigate the prognostic value of magnetic resonance imaging (MRI) findings in the prognosis of patients with leptomeningeal metastasis from lung adenocarcinoma. Methods: Patients with lung adenocarcinoma complicated with cytologically confirmed leptomeningeal metastasis who visited Peking Union Medical College Hospital (blinded for review) between January 2012 and July 2019 were retrospectively reviewed. We collected the patients' clinical and neuroimaging findings and pathological data. The presence of leptomeningeal enhancement on initial contrast MRI was used to divide patients into MRI‐positive and MRI‐negative groups. Univariate and multivariate analyses were performed to evaluate prognostic factors. Results: Eighty‐six patients (38 men and 48 women; median age = 56 [range, 25–80]) were included. Seventy‐three patients (84.9%) had targetable genetic alterations. Only 30 patients (34.88%) had leptomeningeal enhancement on initial contrast MRI. No significant differences were observed in the distribution of demographics, driver gene status, intracranial pressure, complicated brain/spinal metastasis, or treatment strategies between the two groups. The median overall survival of patients in the MRI‐positive group was significantly shorter than that in the negative group (182 days vs. 352 days, p  = 0.036). Cox regression analysis indicated that the presence of leptomeningeal enhancement on the initial diagnostic magnetic resonance imaging was an independent predictor of an unfavourable prognosis of leptomeningeal metastasis (hazard ratio = 1.707, p  = 0.044). Conclusions: This is the first time that positive initial contrast‐enhanced magnetic resonance imaging of the neuroaxis has been proposed as a risk factor for the prognosis of leptomeningeal metastasis from lung adenocarcinoma with contemporary survival data. Abstract : Contrast‐enhanced MRI can be used to estimate the prognosis of patients with leptomeningeal metastasis from lung adenocarcinoma. MRI‐positive patients had a shorter OS.